O processo de documentação pedagógica em uma experiência formativa com professoras na educação infantil: um encontro com o princípio ético - Guimarães, Onileda de Souza Matta (2019)
The present work aims to thematize the pedagogical documentation and the reception of alterity in Early Childhood Education from a formative experience with teachers of this stage of Basic Education. This study was carried out in a kindergarten institution attached to a university in the city of Tubarão, southern Santa Catarina state. The study observed a group of 10 women teachers that worked in Early Childhood Education. In methodological terms, the research is based on a qualitative perspective, proposes the method as deviation, taking the structure of case studies as a way to articulate the empirical to the theoretical. The methodological path was built along the research, researcher and research object together, and was characterized by a formative experience with the teachers during eight meetings that took place from June to November 2018. The purpose of the meetings was to offer a time and space capable of inviting to the construction of pedagogical documentation that narrated the teachers' educational practices. Throughout the meetings, in the course of documenting participant observation, written, photographic, audio-visual registers and, above all, being together, were the research instruments. In dialogue with L. Levinas (1980; 1993), Bárcena e Mèlich, (2000), Hoyuelos (2004), Larrosa (2006), Simiano (2015) e Rinaldi (2017), among others, we sought to build the research analysis. As a result, the importance of the ethical principle in the process of pedagogical documentation is highlighted, because it guides the relationships established between children and adults in the educational routine. At the beginning of the formative experience with the teachers, the images of children were unveiled, pointing, in some situations, to an image of a child that is passive, submissive or subversive of the order established by the adult. The gesture of documenting produced effects of suspending certainties and admitting a possible lack of knowledge about children, a fact that enabled teachers to displace such images and constitute another image of a powerful, active and rightful child. The documentation path led the teachers to move towards children with a hospitable posture, guiding them to rethink everyday situations from this Other who interpellates, summons and calls for responsibility. Being face to face with children and diversity, which questions and generates discomfort, is a great challenge. The formative experience through the pedagogical documentation made the teachers to put themselves in a place of not-knowing, wandering, capable of strangeness and acceptance. This made it possible to establish encounters with the ethical principle of autonomy, responsibility, solidarity, respect for the common good, the environment and diversity. We expect that this analysis extends to the kindergarten the possibility of questioning naturalized assumptions in the pedagogical practice, expanding possibilities of thinking about the path of documentation and the conditions of reception and recognition of the other in the kindergarten.